The effect of ergonomic training and exercise in Esports players: a randomized controlled trial - Gürgan, A.; Sevgin, Ö. (International Journal of Disabilities Sports and Health Sciences, 2024)
This study aimed to investigate the effectiveness of exercises given with ergonomics training on sleep, neck, and upper extremity functions in esports players. Fifty professional or amateur esports players were randomly divided into two groups: an exercise group that received exercise and ergonomics training and a control group that received only ergonomics training. The exercise program was applied three days a week for eight weeks. Before and following the study, the participants were evaluated using the Disabilities of the Arm, Shoulder, and Hand Questionnaire (DASH), the Neck Disability Questionnaire (NDI), the Rapid Upper Extremity Assessment (RULA), and the Pittsburgh Sleep Quality Index (PSQI). Following the implementation of an intervention, there were notable declines in both the NDI and RULA scores in both groups. Conversely, while a reduction in the DASH and PSQI scores was observed in the exercise group, this was not evident in the control group. The decline in NDI and DASH scores in the exercise group following the intervention period was found to be statistically significant when compared to the control group (p < 0.01). The application of physical exercise improving thoracic and shoulder mobility, nerve stretching, and hand/wrist strength and mobility, along with ergonomics training, has been shown to have a positive impact on the neck, upper extremity functions, and sleep quality of the esports players.